Resilience as a shield: Moderating the impact of adverse childhood experiences on emotion regulation in Jakarta’s Generation Z - Dearly; Liviana; Dana Riksa Buana (Universitas Mercu Buana Yogyakarta, 2025)
Generation Z is growing up amid rapid globalization and digital transformation, conditions that shape their psychological well-being and emotion regulation abilities. Nevertheless, Adverse Childhood Experiences (ACEs) remain a significant risk factor. This study aims to examine the moderating role of resilience in the relationship between ACEs and emotion regulation among Generation Z in Jakarta. A total of 227 participants were recruited through purposive sampling, using the ACE-IQ, DERS-SF, and CD-RISC as instruments. Data were analyzed with Moderated Regression Analysis (MRA). The results demonstrate that resilience significantly weakens the negative impact of ACEs on emotion regulation. These findings underscore the importance of resilience-based interventions and open further discussion on practical strategies to enhance adaptive capacity and emotional well-being in young adults who have experienced childhood adversity. Keywords: Adverse childhood experiences, emotion regulation, resilience, Generation Z.